2014
DOI: 10.1177/1076029614523490
|View full text |Cite
|
Sign up to set email alerts
|

Postmarketing Surveillance of Recombinant Human Soluble Thrombomodulin (Thrombomodulin α) in Pediatric Patients With Disseminated Intravascular Coagulation

Abstract: Recombinant human soluble thrombomodulin (thrombomodulin α [TM-α]) has been marketed as a novel anticoagulant for disseminated intravascular coagulation (DIC) in Japan since 2008. Postmarketing surveillance (PMS) has been conducted since its approval. As effectiveness and safety were not previously determined in pediatric patients, this study evaluated PMS data and examined the usefulness of TM-α in treating pediatric DIC. After excluding newborn infants, data for 210 pediatric patients were analyzed and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Failure to detect a significant difference may have been be due to the small sample size, while it might indicate that the trough concentration may not correlate with effectiveness in children. Postmarketing surveillance of TM‐α showed that the DIC resolution rate after administration of TM‐α was 58.5% in children . The rate of achieving the target trough concentration in our study was approximately equivalent to that of DIC resolution found in postmarketing surveillance.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Failure to detect a significant difference may have been be due to the small sample size, while it might indicate that the trough concentration may not correlate with effectiveness in children. Postmarketing surveillance of TM‐α showed that the DIC resolution rate after administration of TM‐α was 58.5% in children . The rate of achieving the target trough concentration in our study was approximately equivalent to that of DIC resolution found in postmarketing surveillance.…”
Section: Discussionsupporting
confidence: 72%
“…Postmarketing surveillance of TM-showed that the DIC resolution rate after administration of TM-was 58.5% in children. 14 The pharmacokinetic values used in this study were for a typical patient who weighed 27 kg. The pharmacokinetic values used in Tsuruta et al's study were for a typical patient who weighed 53.5 kg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant human soluble thrombomodulin (rhTM), which was primarily developed for the treatment of DIC in adults [6], is now widely administered for treating pediatric patients with DIC [7,8]. While previous evidences have shown that the safety and efficacy of rhTM for DIC, recent studies in adults have implicated the efficacy of rhTM on ARDS via anti-inflammatory effects [9,10].…”
Section: Introductionmentioning
confidence: 99%